Cytokine production by monocytes, but not neutrophils, is hampered by long term intensive training in elite swimmers - Teixeira, A. M.; Rama, L.; Morgado, J. M.; Azevedo, S.; Matos, A.; Henriques, A.; Rosado, F.; Alves, F. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
The relationship between exercise and infection incidence may depend on the intensity and duration of the activity. The aim of the present study was to investigate the influence of long term intensive training over the functional features of innate immune cells from high competitive level swimmers, particularly concerning the production of inflammatory mediators. Methods We adopted a single group repeated measures design to study 18 swimmers. Blood samples were collected after 36hours of rest from exercise at four times during the training season: 1) in the beginning of the winter season, after an off training period of 5/6 weeks (t0) 2) after 7 weeks of training (t1) 3) at the 25th week (t2) and 4) at 29th week of training. We looked at the production of IL-1beta, IL-6, IL-12, TNF-alpha and MIP-1beta by neutrophils and monocytes with or without stimulation. The blood samples were incubated in the presence or the absence of LPS and IFN-y and the frequency of cytokine producing cells and the amount of each cytokine produced by cell were evaluated by flow cytometry. Monocytes were identified by the expression of CD33, CD14, HLA-DR and by their FSC and SSC characteristics. Neutrophils were identified by their particular FSC and SSC characteristics and the absence of HLA-DR. Results The frequency and absolute numbers of neutrophils and monocytes did not significantly change during the season with the exception of a decrease in the absolute numbers of monocytes between t0 and t1. Without stimulation, no significant frequencies of cytokine producing cells were observed during the season with the exception of MIP-1beta. The 6h stimulation with LPS and IFN-y, did not induce cytokine expression by neutrophils. The number of cytokine producing monocytes significantly decreased during the season. Additionally the amount of IL-1beta, TNF-alpha and MIP-1beta produced by these cells in response to stimulation also decreased during the training season. The differences were most noticeable between the first (baseline values) and second blood collections, corresponding to the initial increment of training volume. The exceptions were IL-6 and IL-12 that decreased from t0 to t1 but with no statistical significance. Conclusions Our results support the idea that long term intensive training may affect the ability of monocytes to produce important cytokines involved in immune function responses reducing the cells capacity to respond to acute challenges, like an infectious agent, possibly contributing to an elevated risk of upper respiratory tract infections (URTI) episodes in athletes.